Consumers intention to use a single platform e-payment system: A study among malaysian internet and mobile banking users - Chin L.P.; Ahmad Z.A. (ARRAY Development (Canada) Inc., 2023)
This study seeks to explore Malaysian Internet and Mobile banking consumers in adopting a single platform E-payment system using TAM model. This research seeks to investigate whether convenience and design influence perceived ease of use and perceived usefulness. We also investigated the relationship between perceived ease of use, perceived usefulness and perceived risk with consumers intention to use one single platform that integrates card, internet and mobile. Respondents who used boththe Internet and Mobile banking were selected to participate in the survey. AMOS version 22.0 was used to analyze the data. The empirical results suggest that convenience, design, perceived risk, perceived usefulness and perceived ease of use influence consumers intention to use single platform E-payment system. Therefore, convenience, design, perceived risk, perceived usefulness and perceived ease of use should be taken into consideration when designing E-payment system in order to increase the Internet and Mobile banking consumers intention to use. Lai Poey Chin and Zainal Ariffin Ahmad, 2015.